Pengaruh Serat Bambu Jenis Petung (Dendrocalamus Asper) pada Campuran Beton Alir - Devangga, Ramadhan Azzahdewa; Rochmah, Nurul (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Flowing concrete, in accordance with ASTM C 1017 is defined as concrete with a slump flow value greater than 19 cm. However, the use of flowing concrete also presents several challenges, particularly in terms of workability and the need for environmentally friendly materials. Various studies have been conducted on the use of substitute or additive materials in concrete mixtures. This study focuses on flowing concrete mixed with Petung bamboo fibers (Dendrocalamus Asper) to determine the effect of varying bamboo fiber percentages on the slump flow value. The study utilizes Petung bamboo fibers as an additive material. The bamboo fibers, cut into lengths of 5 cm and evenly distributed, were mixed into the flowing concrete. The fiber content variations used were 0%, 3%, 3.5%, 4%, and 4.5%, with a superplasticizer (SP) dosage of 1.5% of the cement weight. The slump flow test results indicate that the higher the percentage of bamboo fiber added, the lower the slump flow value.